AMOR E EDUCAÇÃO EM C. S. LEWIS E JOSEF PIEPER - Starosky, Enio (2015)
Josef Pieper and C. S. Lewis are two of the main philosophers of the 20th century. This research aims to analyse their thoughts on love and their implications to education. Pieper and Lewis are important scholars who have gained enormous respect in the academic world for their original and profound works as christian thinkers. Their studies on love each author from his own point of view are a must for everyone who is concerned with education. Lewis and Pieper share a language-centered methodology that leads to clarify the common essence of loves (Pieper) and the four loves: affection, friendship, eros and charity (Lewis). And both thinkers are focused on ordinary language. The more love is a misunderstood word the more such a philosophical analysis is required. Education for love, according to Lewis and Pieper, is centered in philosophical anthropology, and this dissertation presents the connection between their conception of love and man and the education that follows.